Authoritarian personality, from workers to managers: a study using the RWA scale in Minas Gerais state, Brazil (Gestão & Regionalidade, 2016)
This research compared the authoritarianism level between managers and workers from the industrial and service sectorsof the economy, using a scale called Right-wing authoritarianism - or RWA scale. The theoretical concepts related toauthoritarianism and authoritarian behavior stems from the work presented in The authoritarian personality. We also discussedthe development, deriving from Adorno's F scale, of the RWA scale, today the most widely accepted psychometricinstrument to measure the authoritarian personality. In the survey, the RWA scale was administered to 60 managers (26from the industrial sector and 34 from the service sector) and to 123 operational employees (56 from the industrial sectorand 67 from the service sector), all of them from companies located in the state of Minas Gerais. The comparison showedus a tendency for all groups to express similar levels of authoritarianism, except for the managers of the industrial sector,who showed statistically lower level than the others - something unexpected, considering the theory.